Unveiling university students' acceptance of Microsoft Teams in English courses - Pham, Duc Thuan; Tam, Pham Thi (Universitas Ahmad Dahlan, 2025)
This research investigates university students’ perspectives on Microsoft Teams as a digital platform for English language learning, using the Technology Acceptance Model (TAM) to guide the analysis. The study focuses on four core constructs: perceived usefulness, ease of use, attitude toward using the system, and behavioral intention. Data were gathered from a sample of 270 non-English major students enrolled in various English courses at a Vietnamese university. Quantitative analysis revealed a high overall level of acceptance, with perceived usefulness emerging as the most influential factor. The relationships among TAM components were found to be statistically significant, with perceived usefulness showing a strong effect on students’ attitudes and intentions to continue using the platform. Additionally, students in online learning environments demonstrated more favorable perceptions in terms of ease of use and intention to adopt the tool, compared to those in traditional face-to-face settings. While the findings offer important insights into students' interaction with Microsoft Teams, the study is limited by its single-site context and reliance on self-reported responses, which may introduce bias. To gain a more comprehensive understanding of this learning management system (LMS) adoption, future research should expand to other institutions and explore additional influencing factors such as teaching methods and course content.